Neutralising antibody potency against SARS-CoV-2 wild-type and omicron BA.1 and BA.4/5 variants in patients with inflammatory bowel disease treated with infliximab and vedolizumab after three doses of COVID-19 vaccine (CLARITY IBD): an analysis of a prospective multicentre cohort study. (February 2023) - Liu, Zhigang; Le, Kaixing; Zhou, Xin; Alexander, James L; Lin, Simeng; Bewshea, Claire; Chanchlani, Neil; Nice, Rachel; McDonald, Timothy J; Lamb, Christopher A; Sebastian, Shaji; Kok, Klaartje; et al.
Summary: Background: Anti-TNF drugs, such as infliximab, are associated with attenuated antibody responses after SARS-CoV-2 vaccination. We aimed to determine how the anti-TNF drug infliximab and the anti-integrin drug vedolizumab affect vaccine-induced neutralising antibodies against highly transmissible omicron (B.1.1.529) BA.1, and BA.4 and BA.5 (hereafter BA.4/5) SARS-CoV-2 variants, which possess the ability to evade host immunity and, together with emerging sublineages, are now the dominating variants causing current waves of infection. Methods: CLARITY IBD is a prospective, multicentre, observational cohort study investigating the effect of infliximab and vedolizumab on SARS-CoV-2 infection and vaccination in patients with inflammatory bowel disease (IBD). Patients aged 5 years and older with a diagnosis of IBD and being treated with infliximab or vedolizumab for 6 weeks or longer were recruited from infusion units at 92 hospitals in the UK. In this analysis, we included participants who had received uninterrupted biological therapy since recruitment and without a previous SARS-CoV-2 infection. The primary outcome was neutralising antibody responses against SARS-CoV-2 wild-type and omicron subvariants BA.1 and BA.4/5 after three doses of SARS-CoV-2 vaccine. We constructed Cox proportional hazards models to investigate the risk of breakthrough infection in relation to neutralising antibody titres. The study is registered with the ISRCTN registry, ISRCTN45176516, and is closed to accrual. Findings: Between Sept 22 and Dec 23, 2020, 7224 patients with IBD were recruited to the CLARITY IBD study, of whom 1288 had no previous SARS-CoV-2 infection after three doses of SARS-CoV-2 vaccine and were established on either infliximab (n=871) or vedolizumab (n=417) and included in this study (median age was 46·1 years [IQR 33·6–58·2], 610 [47·4%] were female, 671 [52·1%] were male, 1209 [93·9%] were White, and 46 [3·6%] were Asian). After three doses of SARS-CoV-2 vaccine, 50% neutralising titres (NT50s) were significantly lower in patients treated with infliximab than in those treated with vedolizumab, against wild-type (geometric mean 2062 [95% CI 1720–2473] vs 3440 [2939–4026]; p<0·0001), BA.1 (107·3 [86·40–133·2] vs 648·9 [523·5–804·5]; p<0·0001), and BA.4/5 (40·63 [31·99–51·60] vs 223·0 [183·1–271·4]; p<0·0001) variants. Breakthrough infection was significantly more frequent in patients treated with infliximab (119 [13·7%; 95% CI 11·5–16·2] of 871) than in those treated with vedolizumab (29 [7·0% [4·8–10·0] of 417; p=0·00040). Cox proportional hazards models of time to breakthrough infection after the third dose of vaccine showed infliximab treatment to be associated with a higher hazard risk than treatment with vedolizumab (hazard ratio [HR] 1·71 [95% CI 1·08–2·71]; p=0·022). Among participants who had a breakthrough infection, we found that higher neutralising antibody titres against BA.4/5 were associated with a lower hazard risk and, hence, a longer time to breakthrough infection (HR 0·87 [0·79–0·95]; p=0·0028). Interpretation: Our findings underline the importance of continued SARS-CoV-2 vaccination programmes, including second-generation bivalent vaccines, especially in patient subgroups where vaccine immunogenicity and efficacy might be reduced, such as those on anti-TNF therapies. Funding: Royal Devon University Healthcare NHS Foundation Trust; Hull University Teaching Hospital NHS Trust; NIHR Imperial Biomedical Research Centre; Crohn's and Colitis UK; Guts UK; National Core Studies Immunity Programme, UK Research and Innovation; and unrestricted educational grants from F Hoffmann-La Roche, Biogen, Celltrion Healthcare, Takeda, and Galapagos.